Metody badania elastyczności przedsiębiorstwa - Krupski, Rafał (Methods of the Research on Company Flexibility, 2006)
The article presents the importance of an enterprise flexibility category. According to the literature, three methods of company flexibility identification were presented. In connection with these methods the own original research method was presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 64-72